Goodnight, Corduroy! - Freeman, Don; Wheeler, Jody (New York : Viking, an imprint of Penguin Random House LLC, 2022)
"It's bedtime for Corduroy! Join him as he puts on his pajamas, brushes his teeth, and tucks himself into bed"--
Cover title.
On board pages.
Keywords: Corduroy (Fictitious character) -- Juvenile fiction; Bedtime -- Juvenile fiction; Teddy bears -- Juvenile fiction; Toys -- Juvenile fiction; Corduroy (Fictitious character) -- Fiction; Bedtime -- Fiction; Teddy bears -- Fiction; Toys -- Fiction; Board books; Picture books; Board books